Variation in corticosterone response and corticosteroid binding‐globulin during different breeding sub‐stages in Eurasian tree sparrow (Passer montanus). Issue 1 (2nd December 2015) - Li, Mo; Sun, Yanfeng; Wu, Junzhe; Zhang, Xiaorui; Li, Juyong; Yao, Yao; Liu, Xuelu; Li, Dongming; Wu, Yuefeng
ABSTRACT: In free‐living animals, it has been well demonstrated that the intensity of the adrenocortical response to acute restraint stress can vary with reproductive investment during breeding. The parental care hypothesis posits that the stress response is negatively correlated with parental investment in avian species. To further test this hypothesis, we examined changes in both free and total corticosterone (CORT) at baseline and stress‐induced levels (maximal CORT) and corticosteroid‐binding globulin (CBG) capacities, in both sexes of a multi‐brooded Eurasian tree sparrows ( Passer montanus ), during the nest building, the early nestling, the later egg‐laying, and the later nestling stages. Our results showed Eurasian tree sparrows did not exhibit any differences between sexes in CORT and CBG levels during the egg‐laying or nestling stages. Both sexes had lowered CBG capacities and females exhibited lower maximal CORT during the early compared to later nestling stages. In addition, both sexes had lower maximal free CORT levels during the nest building stage than those of the early nestling stages, and males expressed higher total maximal CORT levels than females during nest building stage. The variation in CORT response and CBG levels during different breeding sub‐stages in Eurasian tree sparrow may correlate with their energetic situations and parental investments. J. Exp. Zool. 325A:75–83, 2016 . © 2015 Wiley Periodicals, Inc.